Peran BPRS Al-Washliyah Dalam Mengangkat UMKM Melalui Program Pembiayaan Syariah Periode 2016-2020 - Andriani, Dwi; Firman, Dody (Universitas Labuhanbatu, 2023)
This research aims to determine the role of PT. BPRS Al-Washliyah Medan in Raising Micro, Small and Medium Enterprises (MSMEs) through sharia financing programs, to find out the number of customers receiving MSME financing nationally and to find out the level of distribution of mudharabah financing from 2016 to 2020. This research is qualitative research. The analytical approach is qualitative descriptive analysis. The data collection techniques used were documentation and interview techniques. The conclusion of this research is that the role of BPRS Al-Washliyah in raising MSMEs can be seen from three things, namely the role of Islamic banks in developing MSMEs which can be seen from the availability of MSMEsÂ financing products, monitoring financing and business development, and the capital building for MSMEs that will be provided. the bank, namely in the form of management assistance and business supervision for customers. The obstacles to BPRS Al-Washliyah in increasing its role in the MSMEsÂ sector in Medan are capital that does not yet meet all business capital needs, collateral as a condition for obtaining financing that is too large, making it difficult for customers to borrow money at the bank, as well as the existence of other sharia banks that offer similar products and Conventional banks offer the same products with low interest which causes competition among these banks. The solution provided is that Indonesian Sharia Banking has a significant role in the national economic system by providing financing to MSMEs entrepreneurs so that they continue to operate and are able to improve people's welfare. Another solution to the problems that arise is to reduce the value of the collateral.